2014
DOI: 10.1128/cvi.00618-14
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Immunogenicity of an Intranasal Sendai Virus-Based Human Parainfluenza Virus Type 1 Vaccine in 3- to 6-Year-Old Children

Abstract: , or 5 ؋ 10 7 50% egg infectious doses) was delivered by the intranasal route to each study participant. The vaccine was well tolerated by all the study participants. There was no sign of vaccine virus replication in the airway in any participant. Most children exhibited an increase in antibody binding and neutralizing responses toward hPIV-1 within 4 weeks from the time of vaccination. In several children, antibody responses remained above incoming levels for at least 6 months after vaccination. Data suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 23 publications
0
45
0
Order By: Relevance
“…We have previously shown that SeV induces rapid and durable B and T cell responses systemically and in upper respiratory tract (URT) and lower respiratory tract (LRT) tissues [36, 37]. Non-recombinant SeV is currently in clinical trials and has been shown to be well tolerated in adults and 3–6 year old children [9, 11]. Tests in 1–2 year old children are ongoing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that SeV induces rapid and durable B and T cell responses systemically and in upper respiratory tract (URT) and lower respiratory tract (LRT) tissues [36, 37]. Non-recombinant SeV is currently in clinical trials and has been shown to be well tolerated in adults and 3–6 year old children [9, 11]. Tests in 1–2 year old children are ongoing.…”
Section: Discussionmentioning
confidence: 99%
“…The unmanipulated virus has already been tested in clinical trials in adults and children as a vaccine for hPIV-1, and has been shown to be well-tolerated and immunogenic. A recombinant SeV carrying HIV genes was also tested clinically, and a recombinant SeV vaccine for respiratory syncytial virus (RSV) is advancing toward clinical trials [914]. Here, we describe the production and testing of a recombinant SeV, named SeV-MPV-Ft that was produced by reverse genetics and carries a gene for a truncated hMPV fusion (F) protein.…”
Section: Introductionmentioning
confidence: 99%
“…SeV has been safely tested as a nonrecombinant Jennerian vaccine against hPIV-1 in adult and pediatric populations [22, 23]. Both SeV-vectored and Ad35-vectored vaccines were well tolerated, and adverse events were not significantly different from those in placebo recipients.…”
Section: Discussionmentioning
confidence: 99%
“…SeV is genetically and antigenically related to hPIV-1 [1821]. A live nonrecombinant SeV vaccine against human parainfluenza virus type 1 (hPIV-1) administered intranasally in adults and young children was safe and immunogenic [22, 23]. SeV antibodies cross-reactive with hPIV-1 antibodies are present in most people [24].…”
mentioning
confidence: 99%
“…In murine studies, SeV could elicit rapid and durable respiratory mucosa and systemic HPIV-specific B cell and T cell responses (Sealy et al, 2010;Rudraraju et al, 2011). Clinical testing of human populations infected with RSV and HPIVs is underway (Adderson et al, 2015). For a full review of current development of antiviral compounds and vaccine candidates tested against RSV, see Costello et al, 2012.…”
Section: Respiratory Syncytial Virus Classification Epidemiology Immentioning
confidence: 99%